2009
DOI: 10.1159/000228254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Posterior Circulation Changes after Revascularization in Patients with Moyamoya Disease

Abstract: Objective: It has been noted that the posterior circulation serves as an important source of collateral blood supply in moyamoya disease. Since most of the literature has focused on non-operative cases and many symptomatic patients receive surgical revascularization, we evaluated the posterior circulation changes after revascularization and found that progressive posterior cerebral artery (PCA) steno-occlusive changes after revascularization caused cerebral hemodynamic compromise and clinical deterioration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 37 publications
4
34
0
1
Order By: Relevance
“…We also found that PCA involvement was a risk factor for postoperative ischemic complications and subsequent strokes, which was similar to prior studies [39,40,41]. In MMD, the leptomeningeal collaterals from the uninvolved PCA generally compensate somewhat for the cerebral blood flow in the ACA or MCA territory [39,42]. However, when steno-occlusive lesions also involve the PCA and decrease the leptomeningeal collaterals to the ACA or MCA territory, postoperative ischemic complications or subsequent infarctions result in that territory [41,42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that PCA involvement was a risk factor for postoperative ischemic complications and subsequent strokes, which was similar to prior studies [39,40,41]. In MMD, the leptomeningeal collaterals from the uninvolved PCA generally compensate somewhat for the cerebral blood flow in the ACA or MCA territory [39,42]. However, when steno-occlusive lesions also involve the PCA and decrease the leptomeningeal collaterals to the ACA or MCA territory, postoperative ischemic complications or subsequent infarctions result in that territory [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that PCA involvement was a risk factor for postoperative ischemic complications and subsequent strokes, which was similar to prior studies [39,40,41]. In MMD, the leptomeningeal collaterals from the uninvolved PCA generally compensate somewhat for the cerebral blood flow in the ACA or MCA territory [39,42].…”
Section: Discussionsupporting
confidence: 90%
“…5,6,11,14,32,34 Preoperative cerebral infarction, younger age at onset, involvement of the PCA, intentional hypotension, high Suzuki stage, and postoperative ischemic events have been observed to correlate with postoperative complications and outcomes. According to the multivariate logistic regression analyses, our study showed that PCA involvement in both groups with no statistically significant differences preoperatively together with the late postoperative stroke was associated with unfavorable clinical outcomes, which was similar to the previous results observed in our center.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Therefore, the postsurgical outcome of neurocognitive function is of interest not only to surgeons but also to patients and parents. Clinical research on the outcome of MMD treatment has examined the degree of revascularization, disappearance of TIAs and general clinical outcome, evaluated by grading scales, such as the modified Rankin Scale [4,5,6]. Previous reports focusing on neurocognitive issues have mentioned that intellectual development is impaired in a certain group of pediatric MMD patients and evaluated the prognostic factors that would be instrumental in determining the postoperative intellectual outcome.…”
Section: Introductionmentioning
confidence: 99%